ANALISIS KINERJA APARATUR DESA DALAM PENGELOLAAN ALOKASI DANA DESA (ADD) PERSPEKTIF EKONOMI ISLAM - Remi Kartina; Amir Mukadar; Aan Zulyanto; Marini Marini (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This research aims to analyze the performance of village officials in managing Village Fund Allocations (ADD) from an Islamic economic perspective. The performance of village officials is an important factor in achieving ADD management goals, namely improving community welfare and sustainable village development. This research uses a qualitative approach with descriptive methods, where data is obtained through interviews, observation and documentation. The research results show that the management of ADD by village officials has generally been carried out in accordance with the principles of accountability and transparency. However, there are several weaknesses, such as a lack of community participation and low understanding of village officials about the principles of Islamic economics, such as justice, efficiency and collective benefit. From an Islamic economic perspective, ADD management must be carried out by prioritizing the values ​​of trust, justice and responsibility to realize community welfare. This research concludes that optimizing the performance of village officials in managing ADD requires increasing human resource capacity, active involvement of the community, and comprehensive application of Islamic economic principles. Recommendations are given to the village government and related parties to strengthen supervision and training regarding ADD management according to Islamic values. Keywords: Village Apparatus Performance, Fund Allocation, Islamic Economics, Financial Management.